A Peculiar People Anti-Mormonism and the Making of Religion in Nineteenth-Century America. - Fluhman, J. Spencer (Chapel Hill : The University of North Carolina Press, 2012)
Though the U.S. Constitution guarantees the free exercise of religion, it does not specify what counts as a religion. From its founding in the 1830s, Mormonism, a homegrown American faith, drew thousands of converts but far more critics. In A Peculiar People, J. Spencer Fluhman offers a comprehensive history of anti-Mormon thought and the associated passionate debates about religious authenticity in nineteenth-century America. He argues that understanding anti-Mormonism provides critical insight into the American psyche because Mormonism became a potent symbol around which ideas about religion.
The Discovery of a Mormon TheologyThe Politics of Expulsion; CHAPTER 4. "Barbarism": Rhetorics of Alienation; Empire(s) in the West; The Problem of Mormon Whiteness; Mormon Women, the Ungrateful Objects of American Pity; CHAPTER 5. "Heresy": Americanizing the American Religion; Mormonism in the Crowd of World Religions; Textbook Mormons and the Weight of Mormon History; Conclusion: Mormonism (Almost) Defanged; Notes; Bibliography; Acknowledgments; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z.
Print version record.
Includes bibliographical references and index.
Keywords: Church of Jesus Christ of Latter-day Saints -- Controversial literature; Mormon Church -- Controversial literature; Church of Jesus Christ of Latter-day Saints -- History; Mormon Church -- History; United States -- Church history -- 19th century; Church of Jesus Christ of Latter Day Saints -- Controversial literature; Church of Jesus Christ of Latter-Day Saints -- History; Mormon Church -- Controversial literature; Mormon Church -- History; United States -- Church history -- 19th century; RELIGION -- Christianity -- Church of Jesus Christ of Latter-day Saints (Mormon); Church of Jesus Christ of Latter-day Saints; Mormon Church; United States; RELIGION / Christianity / Denominations; 1800 - 1899; Electronic books; Church history; Controversial literature; History